PERKEMBANGAN KAJIAN HADIS KESARJANAAN BARAT - Zuhri, Muh. (ULUL ALBAB Jurnal Studi Islam, 2015)
The aim of the article is to trace the development of the Western scholarâ€™s studies on hadith as the second of Islamic sources. It started from the eighteenth century, and was an implication of their study on Islamic history, legal and theology. The most central problem associated with Prophetic hadithÂ has undoubtedly been their authenticity. This issue occupied Muslim specialists since the early classical period. The first generation of Western scholars inclined to doubt the hadith authenticity, and then, followed by the next generation to convince that hadiths are forged. One of the ultimate theories to prove the hadith authenticity is â€œCommon Linkâ€ theory, that hadith is originated from the common link figure, not the prior, moreover the Prophet. There are two or three generations from the figure to the Prophet. However, there is a scholarâ€™s tent to refuse the previous research result on hadith, approving Muslim scholars opinion that most hadiths have been real event of what the Prophet did and said. They demonstrate some evidence by having some research results as the previous generation did.